Butterfly and moth communities differ in their response to habitat structure in rainforests of Mount Cameroon. (17th December 2020) - Delabye, Sylvain; Maicher, Vincent; Sáfián, Szabolcs; Doležal, Jiří; Altman, Jan; Janeček, Štěpán; Kobe, Ishmeal N.; Murkwe, Mercy; Šebek, Pavel; Tropek, Robert
Abstract: Mechanisms structuring tropical communities are still under‐studied, especially in Afrotropical rainforests. Although insect herbivores are considered to depend on plant diversity, we hypothesized that vegetation structure, together with other microhabitat characteristics, can be more important for some insects. Here, we compared habitat associations of fruit‐feeding butterflies and moths, two ecologically different groups of Lepidoptera, in three rainforest localities in foothills of Mount Cameroon, West/Central Africa. Based on a comprehensive dataset of 16, 040 specimens of 398 species systematically collected by 240 traps at 48 plots (altogether 9.68 ha), we analyzed how plant community composition, habitat openness, and forest structure affect communities of butterflies and moths. We expected different habitat descriptors to predict communities of the two insect groups. Habitats of tropical fruit‐feeding moth communities have never been studied before. In both analyses of species richness and community structure, butterfly communities depended mostly on forest openness. Moth species richness depended on plant diversity and forest openness, whilst the latter substantially influenced their community composition. Additionally, we revealed differences in habitat associations between understory and canopy communities of both groups. Whilst species richness of understory communities was not influenced by any habitat characteristics, it generally followed the general patterns in canopies. By contrast, composition of understory communities followed the general patterns, whilst effects of habitat characteristics on canopy communities were minor for butterflies and none for moths. The differences between such closely related groups of herbivorous insects warn against generalization based on single‐taxon studies and highlight the need of community‐wide research of tropical rainforests. Abstract in French is available with online material Abstract : Communities of fruit‐feeding butterflies and moths differed in their use of habitat in tropical rainforests of Mount Cameroon. Butterfly communities depended mainly on forest openness, whilst moths were largely affected by plant communities; these differences are probably related to the different day activity of adults. Résumé: Les mécanismes responsables de la structuration des communautés tropicales sont toujours très insuffisamment étudiés, en particulier dans les for ê ts Afrotropicales. Bien que les insectes herbivores soient généralement considérés comme dépendant principalement de la composition des communautés de plantes, nous posons l'hypothèse que la structure de la végétation, ainsi que d'autres caractéristiques des microhabitats, peuvent ê tre plus importan t pour certains groupes d'insectes. Dans ce travail, les auteurs ont comparé les associations de deux groupes de Lépidoptère se distinguant par leur écologie, les papillons de jour et des papillons de nuit frugivores, au sein de trois localités de forêt tropicale situées au piémont du Mo n t Camerou n, en Afrique de l'Ouest/Centrale. À partir d'un jeu de données complet comprenant 16, 040 spécimens pour 398 espèces systématiquement collectés par 240 pi èges répartis sur 48 points d'échantillonnages (pour une surface totale de 9.68 ha) dans la végétation sous canopée et dans la canopée et pendant trois saisons différentes, les auteurs ont analysé comment la composition des communautés de plantes, l'ouverture de la canopée et de la structure forestière influencent les communautés de papillons de jour et de papillons de nuit. Nous avons supposé que différents facteurs de l'habitat prédisent les deux communautés. Les habitats des communautés de papillons de nuit frugivores tropicaux n'ont jamais été étudiés auparavant. L'analyse de la richesse spécifique et de la structure des communautés de papillons de jour a révélé que ces communautés dépendent principalement de l'ouverture de la canopée. La richesse spécifique des papillons de nuit dépendait de la diversité végétale et de l'ouverture de la canopée, alors que cette dernière influençait considérablement leur composition. De plus, nous avons identifié des différences dans la les associations d'habitat entre la canopée et la sous‐canopée dans les deux communautés. Alors qu'aucun facteur de l'habitat n'a influencé les richesses spécifiques des communautés de sous‐canopée, celles‐ci ont suivi les patterns généraux dans la canopée. En revanche, la composition des communautés de sous‐canopée s'est calquée sur celle des communautés dans leur ensemble, alors que les effets des facteurs de l'habitat ont été mineurs sur la communauté de papillons de jour en canopée, et absents sur celle des papillons de nuit en canopée. Les différences entre ces groupes d'insectes herbivores si proches mettent en garde contre les généralisations issues d'études basées uniquement sur un seul taxon et mettent l'accent sur la nécessité d'étudier des communautés plus larges dans les for ê ts tropicales.